Key Life History Attributes and Removal Efforts of Invasive Lionfish (Pterois volitans) in the Flower Garden Banks National Marine Sanctuary, Northwestern Gulf of Mexico - Blakeway, Raven D.; Fogg, Alexander Q.; Johnston, Michelle A.; Rooker, Jay R.; Jones, Glenn A. (Frontiers in Marine Science, 2022)
Indo-Pacific lionfish (Pterois volitans and P. miles) are the first marine teleost to have successfully invaded and become established in the Western Atlantic Ocean of the United States, Gulf of Mexico (GoM), and Caribbean Sea. Pterois volitans were first reported in the Flower Garden Banks National Marine Sanctuary (FGBNMS), a protected coral reef system in the northwestern GoM, in 2011. Little is understood about the life history characteristics of lionfish in this ecosystem. This study assessed population characteristics (size, density, age and growth) and removal efforts of lionfish (n = 1,665) at two coral reef sites within FGBNMS for 2015, 2016, and 2018. The annual increment formation in sagittal otoliths was examined to assess the age and growth of lionfish collected in 2018 (n = 100). Lionfish ranged in size from 75 to 444 mm total length (TL) and 4–1,153 g in total weight (TW). Six hundred and ten fish were randomly dissected for sex determination (females = 256, males = 354), females ranged in size from 137 to 348 mm TL and 21–586 g, while males ranged from 118 to 444 mm TL and 18–1,153 g. Interannual variation in mean lionfish density ranged from 26.7 individuals per hectare (ind ha–1) in 2016 to 81.1 ind ha–1 in 2018, while removal effort significantly increased ranging from 1.92 to 5.42 kg diver h–1. Lionfish age ranged from 0 to 10 years, with a mean age of 3.9 years. The observed values of the asymptotic maximum total length (L∞) and Brody’s growth coefficient (K) were 345 mm and 0.30 for females and 415 mm and 0.18 for males. Results suggest lionfish from FGBNMS exhibit markedly lower mean densities, a lower L∞ and growth rate, but attain older ages than lionfish in the Caribbean Sea, Western Atlantic Ocean, and other ecoregions in the northern GoM. This study describes the first key life history parameters and removal efforts for lionfish in a protected, healthy coral reef system in the northwestern GoM that may provide insight into environmental population controls (e.g., ecological resilience). Metrics from this study could be integrated into mechanistic ecological models to determine if FGBNMS is in fact exhibiting natural resilience to the lionfish invasion.